Faktor–Faktor Yang Berhubungan Dengan Kepuasan Pasien Hipertensi Di Puskesmas Anak Air Kota Padang Tahun 2024 - Aryanti, Resi; Asyari, Dian Paramitha (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Based on the report from the Health Department of Padang City in 2022, the Anak Air Health Center had the lowest coverage for hypertension services at 7%. The aim of this study is to identify factors associated with patient satisfaction regarding hypertension treatment at the Anak Air Health Center in Padang City in 2024. This quantitative research employs a cross-sectional study design. The study was conducted at the Anak Air Health Center, with a population of 1,501 hypertension patients visiting the center in 2023, from which a sample of 94 individuals was taken using accidental sampling techniques. Data were collected through a questionnaire and analyzed univariately and bivariately using the chi-square test. The results indicated that 66.0% of respondents were dissatisfied with the services, with 66.0% of the reliability dimension rated as poor quality, 69.1% of the responsiveness dimension rated as poor quality, 61.7% of the assurance dimension rated as poor quality, 66.0% of the empathy dimension rated as poor quality, and 67.0% of the tangibles dimension rated as poor quality. Statistical tests showed that all five dimensions of service quality were significantly related to patient satisfaction with a p-value ≤ 0.05. In conclusion, the quality dimensions are associated with hypertension patient satisfaction. It is recommended that the Anak Air Health Center improve service quality and patient satisfaction by providing training for staff, implementing a service waiting time system such as online registration or a digital queue system, establishing standard operating procedures (SOPs) for service delivery, and enhancing the necessary facilities. Keywords: Hypertension, Satisfaction, Service Quality